2012
DOI: 10.1002/jcb.23425
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine externalization and membrane blebbing are involved in the nonclassical export of FGF1

Abstract: The mechanisms of nonclassical export of signal peptide-less proteins remain insufficiently understood. Here we demonstrate that stress-induced unconventional export of FGF1, a potent and ubiquitously expressed mitogenic and proangiogenic protein, is associated with and dependent on the formation of membrane blebs and localized cell surface exposure of phosphatidylserine. In addition, we found that the differentiation of promonocytic cells results in massive FGF1 release, which also correlates with membrane bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…C-terminal HA tag, which does not interfere with FGF1 release [24], was used for immunohistochemical FGF1 detection. To ensure cell type specific FGF1 expression, we chose a Tet-based system.…”
Section: Resultsmentioning
confidence: 99%
“…C-terminal HA tag, which does not interfere with FGF1 release [24], was used for immunohistochemical FGF1 detection. To ensure cell type specific FGF1 expression, we chose a Tet-based system.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it was suggested that the protein complex needs to undergo conformational changes such as partial denaturation before the release [39,40]. Furthermore, the FGF1 release may involve destabilization of the lipid bilayer [8,41], which cannot be described by our model here.…”
Section: Discussionmentioning
confidence: 50%
“…The peripheral translocation of FGF1 is stimulated also by thrombin [48]. The staining of nonpermeabilized stressed cells for externalized FGF1 showed that it is not evenly distributed across the cell membrane but concentrated in distinct oval-shaped domains with the diameters from 0.5 to 5 μm [40]. Most of these FGF1-positive domains are also stained for the acidic phospholipid (PL) phosphatidylserine (PS).…”
Section: Phospholipids and Nonclassically Released Proteinsmentioning
confidence: 99%
“…However, cell stress induces the translocation of FGF1 to the outer leaflet of the PL bilayer [80]. The simultaneous externalization of PS and FGF1 was observed also in U937 promonocytic leukemia cells induced to differentiate to macrophages [40]. Interestingly, the knockdown of PL scramblase 1 (PLSCR1), an enzyme involved in PS transmembrane translocation [81], influenced neither the secretion of FGF1 nor PS externalization [40].…”
Section: Phospholipids and Nonclassically Released Proteinsmentioning
confidence: 99%
See 1 more Smart Citation